Rare cases in herniology: The contents of the hernia – part of the liver, metastatic carcinoma, a foreign body - K. S. Tolkachev (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Surgical treatment of patients with postoperative ventral hernias is one of the most pressing problems in herniology. Verification of the diagnosis of postoperative ventral hernia is usually not difficult. At the same time, there may be difficulties in diagnosis associated with determining the true size of the hernia orifices, the contents of the hernial sac. These moments are  determined by various factors: the location of the hernia on the anterior abdominal wall, the age, sex of the patient, as well as anamnesis of hernia and the volume of surgery previously performed. One of the very rare situations in external abdominal hernias is the situation when the content of  the hernial sac is the part of the parenchymal organ, the tumor process, as well as foreign bodies. The study presents the observation materials of three patients admitted for diagnosis and treatment to the surgical hospital clinics of Irkutsk State Medical University. When examined and treated, it was found that in one case the content of the hernia sac included a part of the left lobe of the liver, in another observation, the inguinal hernia sac contained metastatic carcinoma, in the third case – a foreign body was found. All patients underwent surgery (hernioplasty, hernioplasty). Diagnosis of hernia of the anterior abdominal wall was confirmed. A literary search was made for rare clinical examples in herniology. In the world literature, there are only eight observations when the content of the hernia sac was a part of the lobe of the liver; the presence of metastatic carcinoma and a free foreign body we found as single observations described by known specialists in herniology.